Assessing the Instructional Supervisory Strategies Among Master Teachers for Enhancing Research Productivity Towards Supervision Skills Development Framework in the Department of Education - Dagsa, Bephanie; Alegre, Emybel (East Asian Journal of Multidisciplinary Research, 2024)
This study aimed to assess the research productivity and supervision strategies for the framework development using MASTERp. Additionally, it further identifies the perceived impediments and challenges encountered by these educators. Employing a quantitative methodology, specifically a descriptive correlational research design, the research participants were selected through randomized sampling technique. Data collection was facilitated using survey questionnaire, for the master teachers at elementary, junior high, and senior high levels within public schools in the Surigao del Norte division. The perceived need for supervision skills to enhance research productivity was rated as moderate by the participants, with mentorship and guidance, research planning and goal setting, and collaboration and networking needing attention. Supervision skills were significantly linked to research activities and initiatives, underscoring the importance of continuous professional development in improving these competencies.